Cefepime Therapy for Monomicrobial Enterobacter cloacae Bacteremia: Unfavorable Outcomes in Patients Infected by Cefepime-Susceptible Dose-Dependent Isolates - Lee, Nan-Yao (Antimicrob Agents Chemother, 2015)
A new category of cefepime susceptibility, susceptible dose dependent (SDD), for Enterobacteriaceae, has been suggested to maximize its clinical use. However, clinical evidence supporting such a therapeutic strategy is limited. A retrospective study of 305 adults with monomicrobial Enterobacter cloacae bacteremia at a medical center from 2008 to 2012 was conducted. The patients definitively treated with in vitro active cefepime (cases) were compared with those treated with a carbapenem (controls) to assess therapeutic effectiveness. The 30-day crude mortality rate is the primary endpoint, and clinical prognostic factors are assessed. Of 144 patients receiving definitive cefepime or carbapenem therapy, there were no significant differences in terms of age, sex, comorbidity, source of bacteremia, disease severity, or 30-day mortality (26.4% versus 22.2%; P = 0.7) among those treated with cefepime (n = 72) or a carbapenem (n = 72). In the multivariate analysis, the presence of critical illness, rapidly fatal underlying disease, extended-spectrum beta-lactamase (ESBL) producers, and cefepime-SDD (cefepime MIC, 4 to 8 μg/ml) isolates was independently associated with 30-day mortality. Moreover, those infected by cefepime-SDD isolates with definitive cefepime therapy had a higher mortality rate than those treated with a carbapenem (5/7 [71.4%], versus 2/11 [18.2%]; P = 0.045). Cefepime is one of the therapeutic alternatives for cefepime-susceptible E. cloacae bacteremia but is inefficient for cases of cefepime-SDD E. cloacae bacteremia compared with carbapenem therapy.